2023
DOI: 10.1186/s12872-023-03200-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between albumin corrected anion gap and 30-day all-cause mortality of critically ill patients with acute myocardial infarction: a retrospective analysis based on the MIMIC-IV database

Abstract: Background The anion gap (AG) has been linked to the prognosis of many cardiovascular disorders. However, the correlation between albumin-corrected anion gap (ACAG) and 30 d all-cause mortality of intensive care patients with acute myocardial infarction (AMI) is unclear. Furthermore, owing to the lack of studies, it is also unknown whether ACAG is more accurate than AG in predicting the mortality of AMI. Methods The Medical Information Mart for Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…We demonstrated in this study that ACAG has a better predictive value than AG in the prognostic prediction of S-AKI, which implies that ACAG may be an excellent alternative variable in constructing a scoring system. Meanwhile, the advantage of ACAG over AG may not be an isolated case, but may also be a pattern in other diseases (some studies have already confirmed this, including sepsis [ 20 ], acute pancreatitis [ 21 ], and acute myocardial infarction [ 22 ]), and our study provides more evidence for subsequent studies. Furthermore, this advantage of ACAG over AG has some value in the clinic, and perhaps, in the future, ACAG could be a direct substitute for AG in certain diseases.…”
Section: Discussionsupporting
confidence: 55%
“…We demonstrated in this study that ACAG has a better predictive value than AG in the prognostic prediction of S-AKI, which implies that ACAG may be an excellent alternative variable in constructing a scoring system. Meanwhile, the advantage of ACAG over AG may not be an isolated case, but may also be a pattern in other diseases (some studies have already confirmed this, including sepsis [ 20 ], acute pancreatitis [ 21 ], and acute myocardial infarction [ 22 ]), and our study provides more evidence for subsequent studies. Furthermore, this advantage of ACAG over AG has some value in the clinic, and perhaps, in the future, ACAG could be a direct substitute for AG in certain diseases.…”
Section: Discussionsupporting
confidence: 55%
“… 22 A study similar to our research got the conclusion that ACAG and 30 day all‐cause mortality had a non‐linear relationship, and ACAG had better predictive value in predicting 30 day all‐cause mortality of patients with AMI than the AG. 20 The final inclusion of this article encompassed 2160 eligible patients. The differences in the number of included individuals between our study and this article may be attributed to variations in data collection periods and methods for obtaining AG.…”
Section: Discussionmentioning
confidence: 99%
“…AG, like other laboratory indicators, was directly extracted from the MIMIC database, which was different from previous literature, 20 where AG was calculated using indicators such as sodium, chloride, and bicarbonate. The direct acquisition of AG in this study avoids confounding factors caused by these indicators not being measured at the same time point.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Linhao Jian et al. [ 22 ] revealed that ACAG was more effective than AG in predicting 30-d mortality in ICU patients with acute myocardial infarction (AMI).…”
Section: Introductionmentioning
confidence: 99%